Dynamic volume magnetic domain wall imaging in grain oriented electrical steel at power frequencies with accumulative high-frame rate neutron dark-field imaging. Issue 1 (December 2018) - Harti, Ralph; Strobl, Markus; Schäfer, Rudolf; Kardjilov, Nikolay; Tremsin, Anton; Grünzweig, Christian
Abstract The mobility of magnetic domains forms the link between the basic physical properties of a magnetic material and its global characteristics such as permeability and saturation field. Most commonly, surface domain structure are studied using magneto-optical Kerr microscopy. The limited information depth of approx. 20 nanometers, however, allows only for an indirect interpretation of the internal volume domain structures. Here we show how accumulative high-frame rate dynamic neutron dark-field imaging is able for the first time to visualize the dynamic of the volume magnetic domain structures in grain oriented electrical steel laminations at power frequencies. In particular we studied the volume domain structures with a spatial resolution of ∼100 μm and successfully quantified domain sizes, wall velocities, domain annihilation and its duration and domain wall multiplication in real time recordings at power frequencies of 10, 25 and 50 Hz with ±262.5 A/m and ±525 A/m (peak to peak) applied field.